Ai-based disease prediction: a review: Ai-based disease prediction: a review - Arabboev,, Mukhriddin; Begmatov,, Shohruh; Rikhsivoev,, Mokhirjon; Nosirov, Khabibullo (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Abstract. Artificial intelligence (AI) advancements have enabled the development of innovative approaches for predicting and diagnosing diseases. This paper provides a comprehensive overview of the existing disease prediction methods based on AI. The review paper covers various AI techniques, including machine learning, deep learning, and hybrid models, that are used to predict a wide range of diseases. Keywords: AI, ML, disease prediction, hybrid models